Flourishing Scale: psychometric analysis in cisgender homosexual men - Carranza-Benites, Renzo J. (2024)
Objective: To analyze the evidence of validity of the Flourishing Scale in Peruvian cisgender homosexual men. Methods: Study sample selected through a snowball sampling procedure, using inclusion and exclusion criteria. A total of 307 adults who met the criteria participated in the study and completed the Flourishing Scale. To assess the internal structure of the scale, a confirmatory factor analysis (CFA) was conducted. In addition, internal consistency and evidence of validity in relation to other variables were analyzed. Results: A unidimensional structure and an acceptable reliability were demonstrated. Most of the model fit indices were adequate; however, the RMSEA was high. Conclusion: It is considered that the proposed model can be used since almost all the fit indices were satisfactory.